Development of Digital-Based Teaching Materials (Flipbook) on Basic Block Technique Material in Sepak Takraw - I Komang Bayu Tirta; I Ketut Semarayasa; I Komang Sukarata Adnyana (Universitas Negeri Semarang, 2026)
Sepak takraw is a traditional game originating from Southeast Asia, widely sought after in countries such as Thailand, Indonesia, Malaysia, and Myanmar. The aim of this research is to develop digital flipbook-based teaching materials using basic block techniques using qualitative and quantitative research methods. Results of observations through Google Forms and interviews, which showed that 97.6% of respondents agreed that there was effective and flexible learning innovation. All respondents (100%) also confirmed that flipbook-based digital teaching materials had never been applied in teaching basic sepak takraw techniques using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. Data analysis was conducted descriptively, quantitatively, and qualitatively, with the research subjects being fifth-semester students of the Physical Education, Health, and Recreation Study Program who were selected purposively . The data collection instrument in this study used a questionnaire recording sheet. The results showed that the content/material expert test obtained a very feasible category (100%), the design expert test was feasible (83%), the media expert test was very feasible (98%), and the field practitioner expert test was 98%. The product trial also produced a highly suitable category, with a presentation of 95.4% in individual trials, 96% in small group trials, and 95% in large group trials. Thus, this flipbook-based digital teaching material is considered highly relevant and suitable for use in learning.